(untitled) (Fountain Journal of Natural and Applied Sciences, 2025)
The use of polyethene (PE) in packaging has always been associated with attendant environmental issues. Waste PE was sorted and processed from Fountain University, Osogbo, Osun State, Nigeria. For analysis, bottled water packaging, and nylon water sachets (PE) made of polyethene terephthalate (PET) were cleaned, dried, shredded, and characterised using X-ray diffraction (XRD), differential scanning calorimetry (DSC), and Fourier transform infrared (FT-IR) techniques. Two types of candle waxes (A and B) of different grades 1-4 labelled as (A1–A4), (B1 – B4) and composite tiles A and B (CTAs and CTBs) were made using egg shells as a source of calcium carbonate. Thermal recycling was done by combining PE with stearic acid (SA). O-H stretching bands were detected by FT-IR at 3457 cm-1 (A) and 3449 cm-1 (B), while PE peaks were observed at 2918 cm-1 and 720 cm-1, due to -C-H stretching. The wax characteristics, indicated by the endothermic peaks, were detected by DSC (94.5 °C for A and 99 °C for B). The candles’ qualities were improved by additives. The hot- and cold-water absorption and flammability of the egg-shell-incorporated composite tiles exhibit favourable characteristics, with superior water and heat resistance, compared with the commercial tiles. The blends of SA and PE enhanced the candle performances. This study demonstrated the feasibility of repurposing the waste PE into economically viable products, candles and tiles, and supported the idea of “waste to wealth